A CASE STUDY ON UNETHICAL TEAM LEADERSHIP (International Journal of Scientific Research and Management (IJSRM), 2014)
The case study is on an organizational situation which narrates about a newly joined employee’s ordeal with his team leader. The new joiner’s contribution was unjustly taken away by his team leader as his credit. The employee was afraid to discuss this issue with his team leader due to his positional power in the organization. He also does not want to escalate the issue to senior project manager due to a fear of reprisal. The case study can be used to discuss in organizational behavior sessions for post graduates and undergraduates to provide insight on the leadership style, positional power, organizational ethics and procedural justice.